Morphological Examination of Young Adults Related to Obesity - Borsos,Éva (Sociedad Chilena de Anatomía, 2018)
SUMMARY: This study presents a cross-board comparison of the morphological characteristic of students of the Hungarian Language teacher training faculty in Subotica, Serbia based on their nutritional status estimate of their nourishment state. The sample was composed by 146 young adults from all four study years of the faculty, ranging from age 19 to 23. The following anthropometric measurements were carried out: body weight, height, skin fold thickness (skin folds measured at the scapula, triceps, biceps, ilium, hip, thigh and abdomen) and circumferences (waist, hip). The authors calculated and analyzed the data, including: the BMI (body mass index) with the formula, skin fold thickness and with 4-Site Skin fold Equation and waist hip ratio. Descriptive statistic was used to describe the morphological characteristics. Independent T-test and ANOVA analysis was performed to compare the students according to sex and age. The main results of the present study are: (1) no significant difference is found between the age groups in the case of either height or body weight, not for the young men or the young women in the study; (2) the differences between height and weight in the case of the male and female as characteristic for this age group can be observed; (3) the female students are more often found to be overweight or obese than the male students; (4) the majority of participant students can be classified into the normal nutritional status’ category, which holds true for both the young men and women of the study; (5) the fat percentages calculated based on skin fold values show that in terms of weight, the majority of the female students fall under the ‘acceptable’ category, while the majority of the young men are classed as ‘thin’; (6) in the case of abdominal overweight 20.0 % of men and 19.48 % of women belong to the category ‘obese’. This information about the students of the teacher training program is vital, as these young men and women will play an important role as future teachers and thereby, as role models helping to prevent childhood obesity and guiding children throughout their education towards a healthy life style.